Properties of a Mutant of Escherichia coli with a Temperature-sensitive Fructose-1,6-Diphosphate Aldolase - Böck, August (1966)
Böck, August (Purdue University, Lafayette, Ind.), and Frederick C. Neidhardt. Properties of a mutant of Escherichia coli with a temperature-sensitive fructose-1,6-diphosphate aldolase. J. Bacteriol. 92:470–476. 1966.—A mutant of Escherichia coli in which fructose-1,6-diphosphate aldolase functions at 30 C but not at 40 C was used to study the physiological effect of a specific block in the Embden-Meyerhof glycolytic pathway. Growth of the mutant at 40 C was found to be inhibited by the presence of glucose or certain related compounds in the medium. At 40 C, glucose was metabolized at 30 to 40% of the control rate and was abnormal in that glucose was converted into other six-carbon substances (probably gluconate, in large part) that were released into the culture medium. The inhibition was complete, but transient; its duration depended upon the initial amount of inhibitor added. The resumption of growth at 40 C was correlated with the further catabolism of the excreted compounds. When glycerol was used to grow the mutant at 40 C, the growth inhibition by glucose was accompanied by cessation of glycerol metabolism. Growth on α-glycerol phosphate was not inhibited under these conditions, implicating glycerol kinase as a possible site of inhibition; no inhibition of glycerol kinase by sugar phosphates, however, could be detected in vitro. The inhibitory effect of glucose on growth at 40 C is not caused by a deficit of intracellular adenosine triphosphate, but may be the result of a generalized poisoning of many cell processes by a greatly increased intracellular concentration of fructose-1,6-diphosphate, the substrate of the damaged enzyme.